2008
DOI: 10.1002/rcm.3798
|View full text |Cite
|
Sign up to set email alerts
|

Using solvent‐free sample preparation to promote protonation of poly(ethylene oxide)s with labile end‐groups in matrix‐assisted laser desorption/ionisation

Abstract: Protonation is usually required to observe intact ions during matrix-assisted laser desorption/ionization (MALDI) of polymers containing fragile end-groups while cation adduction induces chain-end degradation. These polymers, generally obtained via living free radical polymerization techniques, are terminated with a functionality in which a bond is prone to homolytic cleavage, as required by the polymerization process. A solvent-free sample preparation method was used here to avoid salt contaminant from the so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 17 publications
(32 citation statements)
references
References 62 publications
1
30
1
Order By: Relevance
“…Other examples of spontaneous dissociation in the MALDI source were reported by Charles and co‐workers for a variety of SG1‐terminated polymers (Mazarin, Phan, & Charles, ; Girod et al, ; Barrere et al, ). Based on data obtained by performing collision‐induced dissociation (CID) of intact electrosprayed alkali adducts to mimic their activation during MALDI, this research group proposed different structures, arising from alternative degradation mechanisms, for the observed modified end‐groups.…”
Section: Maldi‐ms Of Nmp Polymersmentioning
confidence: 81%
See 2 more Smart Citations
“…Other examples of spontaneous dissociation in the MALDI source were reported by Charles and co‐workers for a variety of SG1‐terminated polymers (Mazarin, Phan, & Charles, ; Girod et al, ; Barrere et al, ). Based on data obtained by performing collision‐induced dissociation (CID) of intact electrosprayed alkali adducts to mimic their activation during MALDI, this research group proposed different structures, arising from alternative degradation mechanisms, for the observed modified end‐groups.…”
Section: Maldi‐ms Of Nmp Polymersmentioning
confidence: 81%
“…Interestingly, Schulte et al showed that, despite the use of a saturated NaBF 4 salt solution together with 2,5‐DHB, the shortest chains ( M n < 1,000 g mol −1 ) of the nitroxide‐capped PNIPAM studied could also be generated as intact protonated molecules upon MALDI (Schulte et al, ). Trihydroxyacetophenone (THAP) was also shown to enable production of protonated NMP molecules in MALDI, as reported for TEMPO‐capped polyethylene (Lopez et al, ) as well as for small SG1‐terminated PEO by implementing a salt‐free, solvent‐free sample preparation method (Trimpin et al, ) to avoid salt contaminant from the solvent traditionally used in the dried‐droplet procedure (Mazarin, Phan, & Charles, ).…”
Section: Maldi‐ms Of Nmp Polymersmentioning
confidence: 98%
See 1 more Smart Citation
“…The energy level involved in the MALDI process is indeed sufficient to induce spontaneous homolysis of the intrinsically fragile bond between the last monomer and the nitroxide end-group of NMP polymers [18], preventing intact species to be detected. One exception was however reported in the case of protonated species: for SG1-terminated poly(ethylene oxide), protonation of the nitroxide nitrogen was shown to increase the C ON bond dissociation energy and allowed intact species to be generated in the gas phase upon MALDI [24,25]. Here, lack of intact protonated SG1-terminated P4VP hence indicated that the adducted proton was not located in the nitroxide end-group but most probably on a pyridine pendant group, consistent with the high basicity of these moieties.…”
Section: Maldi-ms Of Nitroxide-terminated P4vpmentioning
confidence: 93%
“…Therefore, there is growing interest in solvent‐free strategies in MALDI sample preparation, with the development of the 'solvent‐free' or 'evaporation grinding' methods . Solvent‐free preparation was also used to analyze fragile compounds when a solvent‐based strategy failed …”
mentioning
confidence: 99%